2017
DOI: 10.1136/gutjnl-2017-315402
|View full text |Cite
|
Sign up to set email alerts
|

Wild type Kirsten rat sarcoma is a novel microRNA-622-regulated therapeutic target for hepatocellular carcinoma and contributes to sorafenib resistance

Abstract: KRAS is dysregulated in HCC by loss of tumour-suppressive microRNA-622, contributing to tumour progression, sorafenib sensitivity and resistance. KRAS inhibition alone or in combination with sorafenib appears as novel promising therapeutic strategy for HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
131
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(140 citation statements)
references
References 50 publications
(20 reference statements)
9
131
0
Order By: Relevance
“…For instance, Wu et al found that adrenergic receptorβ2 activated AKT signaling to facilitate glucose metabolism reprogramming through mediating hypoxia‐inducible factor‐1α (HIF‐1α) stabilization, which resulted in acquired sorafenib resistance both in vivo and vitro . In addition, Dietrich et al uncovered that dysregulation in the upstream mediator of PI3K/AKT, KRAS, led to sorafenib acquired resistance caused by loss of tumor suppressive microRNA‐622 . Aside from this, we previously demonstrated that the occurrence of primary resistance after temporary sorafenib stimulation was attributed to activation of AKT signaling for facilitating cell survival, indicating that the activation of AKT was not only implicated in the acquired resistance of sorafenib treatment but also highly connected to sorafenib primary resistance, which is in accordance with previous studies .…”
Section: Discussionmentioning
confidence: 86%
“…For instance, Wu et al found that adrenergic receptorβ2 activated AKT signaling to facilitate glucose metabolism reprogramming through mediating hypoxia‐inducible factor‐1α (HIF‐1α) stabilization, which resulted in acquired sorafenib resistance both in vivo and vitro . In addition, Dietrich et al uncovered that dysregulation in the upstream mediator of PI3K/AKT, KRAS, led to sorafenib acquired resistance caused by loss of tumor suppressive microRNA‐622 . Aside from this, we previously demonstrated that the occurrence of primary resistance after temporary sorafenib stimulation was attributed to activation of AKT signaling for facilitating cell survival, indicating that the activation of AKT was not only implicated in the acquired resistance of sorafenib treatment but also highly connected to sorafenib primary resistance, which is in accordance with previous studies .…”
Section: Discussionmentioning
confidence: 86%
“…ncRNAs are emerging key regulators of post-transcriptional activity in cancers. miRNAs are most frequently studied and some of them have been proved to be significantly dysregulated in HCC, promoting tumor progression and sorafenib resistance [83,84]. Consistent with the idea that certain cell states determine drug sensitivity, miRNAs, as well as other ncRNAs including lncRNAs that mostly act as sponges of miRNAs, modulated sorafenib sensitivity through regulating EMT and stemness in HCC [85].…”
Section: Post-transcriptional Regulationmentioning
confidence: 87%
“…Loss of wild‐type KRAS occurs upon tumor progression due to overcoming oncogenic form of KRAS (i.e., mutant form) causing allelic imbalance (Ambrogio et al, ), so rescuing wild‐type KRAS can be therapeutic for some types of cancers. For hepatocellular carcinoma (HCC), this approach has failed because of showing a positive relation between high expression of wild‐type KARS with poor patient survival and advanced tumor size (Dietrich et al, ).…”
Section: Mapk Signalingmentioning
confidence: 99%
“…There are strong evidences for cancer type and grade dependency of MAPK mutational profile. KRAS mutation in HCC is rare, compared with other types of cancers (Dietrich et al, ), while for NSCLC this rate is high (Kitajima and Barbie, ), and it reaches to over 90% in PDAC patients (Muzumdar et al, ). Oncogenic mutations of NRAS commonly occur in myeloid leukemia (Kunimoto et al, ).…”
Section: Mutation and Activity Of Mapk Pathway Is Influenced From Canmentioning
confidence: 99%